The emerging roles of long non-coding RNA in host immune response and intracellular bacterial infections - Arunima, Aryashree; van Schaik, Erin J.; Samuel, James E. (Frontiers in Cellular and Infection Microbiology, 2023)
The long non-coding RNAs (lncRNAs) are evolutionarily conserved classes of non-coding regulatory transcripts of > 200 nucleotides in length. They modulate several transcriptional and post-transcriptional events in the organism. Depending on their cellular localization and interactions, they regulate chromatin function and assembly; and alter the stability and translation of cytoplasmic mRNAs. Although their proposed range of functionality remains controversial, there is increasing research evidence that lncRNAs play a regulatory role in the activation, differentiation and development of immune signaling cascades; microbiome development; and in diseases such as neuronal and cardiovascular disorders; cancer; and pathogenic infections. This review discusses the functional roles of different lncRNAs in regulation of host immune responses, signaling pathways during host-microbe interaction and infection caused by obligate intracellular bacterial pathogens. The study of lncRNAs is assuming significance as it could be exploited for development of alternative therapeutic strategies for the treatment of severe and chronic pathogenic infections caused by Mycobacterium, Chlamydia and Rickettsia infections, as well as commensal colonization. Finally, this review summarizes the translational potential of lncRNA research in development of diagnostic and prognostic tools for human diseases.